Cities and Energy: Urban Morphology and Residential Heat-Energy Demand. (February 2014) - Rode, Philipp; Keim, Christian; Robazza, Guido; Viejo, Pablo; Schofield, James
Our aim is better understanding of the theoretical heat-energy demand of different types of urban form at a scale of 500 m × 500 m. The empirical basis of this study includes samples of dominant residential building typologies identified for Paris, London, Berlin, and Istanbul. In addition, archetypal idealised samples were created for each type through an analysis of their built form parameters and the removal of unwanted 'invasive' morphologies. The digital elevation models of these real and idealised samples were run through a simulation that modelled solar gains and building surface energy losses to estimate heat-energy demand. In addition to investigating the effect of macroscale morphological parameters, microscale design parameters, such as U-values and glazing ratios, as well as climatic effects were analysed. The theoretical results of this study suggest that urban-morphology-induced heat-energy efficiency is significant and can lead to a difference in heat-energy demand of up to a factor of six. Compact and tall building types were found to have the greatest heat-energy efficiency at the neighbourhood scale while detached housing was found to have the lowest.